KEPATUHAN WAJIB PAJAK UMKM DI KABUPATEN BADUNG BERDASARKAN PERSEPSI KEPERCAYAAN WAJIB PAJAK DAN KEKUASAAN OTORITAS PAJAK - Ni Luh Gede Desy Ardiani; Sulfan (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2022)
The ratio of submission of Annual Tax Returns at two Tax Service Offices with the working area of Badung Regency is still relatively low when compared to national tax compliance. With more than a quarter of the population owning MSMEs, MSME taxpayer compliance in Badung Regency is an interesting phenomenon to study. This qualitative research aims to determine the compliance of MSME taxpayers seen from the perception of trust in the government and the power of the tax authorities in accordance with the slippery slope framework theory by Kirchler, et al (2008). Collecting data using in-depth interview techniques with 13 informants consisting of 8 MSME taxpayers in Badung Regency, 1 academician, and 4 practitioners as a form of triangulation. This study found that even though trust in the government was not high, MSME taxpayers remained voluntarily compliant as long as they had income and for the convenience of their business. On the other hand, coercive power, especially sanctions and supervision, has more dominant influence than persuasive power. Taxpayers with the post-conventional moral stage are more affected by persuasive power than those in the pre-conventional stage. The results of this study are expected to assist the tax authorities in making policies to improve taxpayer compliance.